Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-74581-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution Algorithm Based on Simulated Annealing

Abstract: Differential evolution algorithm is a simple stochastic global optimization algorithm.In this paper, the idea of simulated annealing is involved into original differential evolution algorithm and a simulated annealing-based differential evolution algorithm is proposed. It is almost as simple for implement as differential evolution algorithm, but it can improve the abilities of seeking the global excellent result and evolution speed. The experiment results demonstrate that the proposed algorithm is superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Excellent samples that will move into the next generation of population groups are used as the empirical analysis samples of structural equation model (SEM) based on Bootstrap selfextraction technique. The main purpose of differential evolution algorithm is to search for individual samples with good fault-tolerant and strong learning ability, so that better individuals with strong learning ability will enter into the next generation groups to maximize the overall search function (Li, Guo, Li, & Liu, 2016;Guo, Li, & Li, 2014;Deb, 2000). Based on the collected samples of 500 university professional teachers, this paper uses differential evolution algorithm, and uses software Matlab and software Stata to set executive parameters, as shown in Table 3.…”
Section: Reliability Test and Validity Test Of Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Excellent samples that will move into the next generation of population groups are used as the empirical analysis samples of structural equation model (SEM) based on Bootstrap selfextraction technique. The main purpose of differential evolution algorithm is to search for individual samples with good fault-tolerant and strong learning ability, so that better individuals with strong learning ability will enter into the next generation groups to maximize the overall search function (Li, Guo, Li, & Liu, 2016;Guo, Li, & Li, 2014;Deb, 2000). Based on the collected samples of 500 university professional teachers, this paper uses differential evolution algorithm, and uses software Matlab and software Stata to set executive parameters, as shown in Table 3.…”
Section: Reliability Test and Validity Test Of Scalementioning
confidence: 99%
“…The related principles, modeling steps and processes of differential evolution algorithm are as follows (Li, Guo, Li, & Liu, 2016;Guo, Li, & Li, 2014;Deb, 2000). Differential evolution algorithm includes four basic operations: population initialization, variation, crossover and selection, and the modeling steps and processes are population initialization, variation based on difference, crossover, selection, termination, output, feedback (Li, Guo, Li, & Liu, 2016;Guo, Li, & Li, 2014;Deb, 2000).…”
Section: Reliability Test and Validity Test Of Scalementioning
confidence: 99%
See 1 more Smart Citation
“…DE employ only three parameters as input to control the searching process, which is less than SA and GA. DE is currently among the most popular metaheuristics for solving single-objective optimization problems within continuous search spaces [20]. DE is generally a simple, and powerful algorithm that can outperform GA in many numerical single-objective optimization problems [40]. DE is able to explore the decision space more efficiently than GA even when multiple objectives need to be optimized [41].…”
Section: Critical Analysismentioning
confidence: 99%
“…Finally, the fitness of the resulting solutions is evaluated in the selection process and the target vector of the population competes against a trial vector to determine which one will be retained in the next generation, as shown in Equation (40). The operation procedure of DE is similar to that of GA but has a small difference with GA in the mutation period.…”
Section: Differential Evolution Algorithmmentioning
confidence: 99%